Reversing Post-Infectious Epigenetic-Mediated Immune Suppression - Abhimanyu,; Ontiveros, Carlos O.; Guerra-Resendez, Rosa S.; Nishiguchi, Tomoki; Ladki, Malik; Hilton, Isaac B.; Schlesinger, Larry S.; DiNardo, Andrew R. (Frontiers in Immunology, 2021)
Epigenetic changes limit the immune response from inducing exuberant collateral damage to host tissue after severe and chronic infections. However, following treatment for these infections, including sepsis, pneumonia, hepatitis B, hepatitis C, HIV, tuberculosis (TB) or schistosomiasis, detrimental epigenetic scars persist, and result in long-lasting immune suppression. This is believed to be one of the contributing factors for why survivors of infection have increased all-cause mortality and increased rates of unrelated secondary infections. Several mechanisms that induce epigenetic-mediated immune suppression have been demonstrated in-vitro and in animal models. Modulation of the AMPK-mTOR, NFAT or NR4A pathways is able to block or reverse the development of detrimental epigenetic scars. Similarly, drugs that directly modify epigenetic enzymes, such as those that inhibit histone deacetylase (HDAC) inhibitors, DNA hypomethylating agents or modifiers of the Nucleosome Remodeling and DNA methylation (NuRD) complex or Polycomb Repressive Complex (PRC) have demonstrated capacity to restore host immunity in the setting of cancer-, LCMV- or murine sepsis-induced epigenetic-mediated immune suppression. A third clinically feasible strategy for reversing detrimental epigenetic scars are bioengineering approaches to either directly reverse the detrimental epigenetic marks or to modify the epigenetic enzymes or transcription factors that induce detrimental epigenetic scars. Each of these approaches, alone or in combination, have ablated or reversed detrimental epigenetic marks in in-vitro or in animal models; translational studies are now required to evaluate clinical applicability.